The Impact of Investment Decisions, Funding Strategies, and Financial Performance on Firm Value: The Moderating Role of GCG - Erpina, Evi; Budhiarto, Ahmad Rizal; Mardiyani, Mardiyani (Yayasan Ilomata, 2025)
This study aims to analyze the impact of investment decisions, funding strategies, and financial performance on firm value in the Indonesian banking sector, while examining the moderating role of Good Corporate Governance (GCG) using Moderated Regression Analysis (MRA). Data were collected from banking companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023 through purposive sampling. The analysis was conducted using MRA to examine the relationships between the independent variables (investment decisions, funding strategies, and financial performance), the dependent variable (firm value), and the moderating interactions of GCG. The results show that investment decisions have an effect but are not significant on firm value, while funding strategies and financial performance have a significant influence. The key finding from the moderation analysis reveals that GCG strengthens the relationship between financial performance and firm value. However, GCG fails to moderate the relationship between investment decisions and firm value, as well as between funding strategies and firm value. The implications of this study emphasize the importance of implementing GCG to enhance firm value through optimizing funding strategies and improving financial performance. For practitioners, these findings encourage the integration of GCG principles into financial decision-making. At the same time, for regulators, the results can serve as a basis for formulating policies that support better GCG implementation in the banking sector. For academics, this research provides a foundation for further studies on factors influencing firm value and the role of GCG across various industries